Influence of Variations of Experimental Conditions and Methods on the Quantification of Nitrous Oxide (N2O) Emissions in Sugarcane: a Meta-Analysis - Valencia Molina, Manuel C. (2024)
Quantifying and analyzing nitrous oxide (N2O) emissions from sugarcane-cultivated soils is a priority issue due to its potential role in climate change in the coming decades. However, understanding the impact of this crop on global N2O emissions is complicated by the variety of experimental conditions and methods used to quantify these emissions. This study aimed to determine the influence of experimental conditions and methodological approaches on quantifying of N2O emissions in soils used for sugarcane production. For this purpose, a meta-analysis of quantitative information on this topic, and published-online up to December 2020 was performed. The average daily N2O emission rate calculated in this research was higher than similar studies and the differences were attributed to methodological differences with these references. In addition, results showed that variables associated with sampling and gas concentration measurement had no significant effects on daily mean N2O emissions. The evaluation period, soil texture, and the management of synthetic N sources and application rates were the main variables affecting N2O emissions. Among the important sugarcane-producing countries United States and India had significantly higher daily mean N2O emission (4.5 ± 1.4 and 3.08 ± 0.08 mg N2O–N m−2 d−1, respectively) than the global average (1.98 ± 0.4 mg N2O–N m−2 d−1). High N2O emissions were widely documented in coarse or intermediate-texture soils. It is recommended that to reduce the uncertainty associated with the estimation of cumulative N2O emissions the monitoring of N2O emissions should include multiple complete growing seasons and include high sampling frequency around the main management practices. The strategies to reduce emissions should focus on the exploration of alternative N fertilizers to urea in sub-traditional doses for sugarcane areas with coarser textured soils. This work provides an important reference framework for the design and development of future research focused on the assessment of N2O mitigation options for sugarcane.